Optimization of a protease extraction using a statistical approach for the production of an alternative meat tenderizer from Manihot esculenta roots - Ahmad, Mohammad Norazmi; Nik Hilmi, Nik Husna; Abdullah, Erna Normaya; Yarmo, Mohd Ambar; Ku Bulat, Ku Halim (Springer India, 2020)
Meat tenderness is the most important criterion in food quality because it strongly inﬂuences the consumer’s satisfaction. Tenderness generally depends on connective tissue and sarcomere length of muscle. One of the effective methods for meat tenderizing is protease treatment. In this study, Manihot esculenta root was chosen as a protease source due to its skin blistering effect, suggesting the presence of strong proteolytic activity. The extraction of the crude protease was optimized by using response surface methodology (RSM) with four independent variables, which were pH (X1), CaCl2 (X2), Triton X-100 (X3) and 2-mercaptoethanol (X4). Based on the RSM model, all the independent variables were signiﬁcant and the optimum extraction conditions were pH 9, 3.24 mM CaCl2, 4.12% Triton X-100 and 6.32 mM 2-mercaptoethanol. Tukey’s test results showed that the difference between the expected and experimental protease activity value was 0.05%. A reduction of meat ﬁrmness was observed when samples treated with enzyme were compared with a control by using a texture analyser. Electrophoretic patterns also showed extensive proteolysis and a reduction of intensity and number of the protein bands in the treated sample. SEM clearly revealed the degradation of muscle ﬁbres and connective tissue of meat treated with crude protease.